DHA supplementation and pregnancy complications - Jiang, Yi; Chen, Yuting; Wei, Lijie; Zhang, Huiting; Zhang, Jingyi; Zhou, Xuan; Zhu, Shenglan; Du, Yuanyuan; Su, Rui; Fang, Chenyun; Ding, Wencheng; Feng, Ling (Journal of translational medicine, 2023)
Docosahexaenoic acid (DHA) supplementation is recommended for women during pregnancy because of its neurological, visual, and cognitive effects. Previous studies have suggested that DHA supplementation during pregnancy may prevent and treat certain pregnancy complications. However, there are contradictions in the current related studies, and the specific mechanism by which DHA acts remains unclear. This review summarizes the research on the relationship between DHA intake during pregnancy and preeclampsia, gestational diabetes mellitus, preterm birth, intrauterine growth restriction, and postpartum depression. Furthermore, we explore the impact of DHA intake during pregnancy on the prediction, prevention, and treatment of pregnancy complications as well as its impact on offspring neurodevelopment. Our results suggest that there is limited and controversial evidence for the protective effect of DHA intake on pregnancy complications, with the exception of preterm birth and gestational diabetes mellitus. However, additional DHA supplementation may improve long-term neurodevelopmental outcomes in the offspring of women with pregnancy complications.